Assessing the relationship between the distress levels in patients with irreversible terminal delirium and the good quality of death from the perspective of bereaved family - Pei Zhou; Cheng Tang; Jingyi Wang; Chunhua Zhang; Jun Zhong (BMC Palliative Care)
Abstract Background Research on achieving a good death for terminally delirious patients is scarce, with limited knowledge about the level of good death and influencing factors. This study investigates the level of good death among delirium patients, factors influencing it, and the correlation between distress, end-of-life care needs, and achieving a good death by surveying bereaved family members of deceased patients in Chinese hospitals. Methods This cross-sectional study from January 2022 to January 2024 was conducted among bereaved family members of patients using an online questionnaire. The questionnaires consisted of (1) participants’ demographic and disease-related questionnaires; (2) the Good Death Inventory (GDI) China version; (3) Terminal Delirium-Related Distress Scale (TTDS) China version; (4) the Care Evaluation Scale - short form (CES) China version. All data were analyzed using descriptive statistics, and the associated factors influencing good death were analyzed by multiple linear regression analyses. Result A total of 263 subjects were enrolled. More males (63.5%) participated than females (36.5%), the mean age was 75.35 ± 13.90 years. Good quality of death was significantly and negatively related to the distress in patients with irreversible terminal delirium (r = -0.458, P<0.01).The multiple linear regression model indicates that TDDS score, CES score, types of diseases, smoking history, nutritional deficiency are important factor affecting the good quality of death. Conclusions The good quality of death from the perspective of bereaved family, a negative correlation was found between the distress in patients with irreversible terminal delirium and good death. Medical staff should be more aware of good quality of death in patients, future research should expand sample sizes to include more demographic data, and explore the concept of a good death across different cultural contexts.